Pharmacokinetics and Bioavailability Study of Tubeimoside I in ICR Mice by UPLC-MS/MS - Lianguo Chen; Qinghua Weng; Feifei Li; Jinlai Liu; Xueliang Zhang; Yunfang Zhou (Journal of Analytical Methods in Chemistry)
The aim of this study is to establish and validate a rapid, selective, and sensitive ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method to determine tubeimoside I (TBMS-I) in ICR (Institute of Cancer Research) mouse whole blood and its application in the pharmacokinetics and bioavailability study. The blood samples were precipitated by acetonitrile to extract the analytes. Chromatographic separation was performed on a UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm). The mobile phase consisted of water with 0.1% formic acid and methanol (1 : 1, v/v) at a flow rate of 0.4 mL/min. The total eluting time was 4 min. The TBMS-I and ardisiacrispin A (internal standard (IS)) were quantitatively detected by a tandem mass spectrometry equipped with an electrospray ionization (ESI) in a positive mode by multiple reaction monitoring (MRM). A validation of this method was in accordance with the US Food and Drug Administration (FDA) guidelines. The lower limit of quantification (LLOQ) of TBMS-I was 2 ng/mL, and the calibration curve was linearly ranged from 2 to 2000 ng/mL (r2 ≥ 0.995). The relative standard deviation (RSD) of interday precision and intraday precision was both lower than 15%, and the accuracy was between 91.7% and 108.0%. The average recovery was >66.9%, and the matrix effects were from 104.8% to 111.0%. In this assay, a fast, highly sensitive, and reproducible quantitative method was developed and validated in mouse blood for the first time. The absolute availability of TBMS-I in the mouse was only 1%, exhibiting a poor oral absorption.